DERIVASI BAHASA MELAYU KUPANG - Emmy Renoat (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
This study focus on derivation in Kupang malay language. Two problems that underline this study are (1) what is word class in Kupang Malay Language that unde goes to the process of derivation (2) How is the derivation morpheme in Kupang malay language. Analysis is done on data that is gained from speakers using Kupang malay language. A description qualitative research method with opportion thecnique. The study has been found that derivation occurs because of a process of affixation eith the addition of several prefics. Prefics attached to a basic meaning ba-, pa-, par-, and ta-. the addition of prefix ba- on nouns as a basic word class to new word classes are verb and adjective.whereans in a basic adjective class, the prefix ba- on adjective base world class has change to a new world class into nouns. Derivation of noun with the addition of par- prefix change the form,meaning dan class of new word into adjectiva. A verb derivation with an addition prefix ta- changging the form, meaning and a new word class from verb become adjectiva. The process of derivation is generally can be formulated. The meaning resulted by the process of derivation in Kupang malay language also change based on the meaning stated by the basic word.